'Safe Ships and Clean Seas': Evading a mandatory shipping code for Antarctic waters - Jabour, JA (International Law Group, School of Law, University of Canterbury, 2009)
Shipping is an inherently dangerous activity, with heightened risks in polarwaters owing to inadequate charts, extreme weather and the presence oficebergs and sea ice, among other factors. In this context, there are currentlytwo proposals before the Internatio nal Maritime Organization (IMO)designed to addtess and mitigate these risks: first, the adoption of voluntaryguidelines for ships operating in polar waters;I second the development of amandatory polar shipping code.' These initiatives respond to the recentgrounding of vessels within the Antarctic Peninsula region and the sinking of the MS Exp lore r south of King George Island in November 2007.3l Understandably, stakeholders are concerned about the future management and regulatory options which are under consideration given the existingproblems of operating within the Antarctic region. These existing challengesare likely to be exacerbated by climate change, which is predicted to affect theformation, composition, extent and duration ofAntarctic sea ice.'